The impact of employer brand discrepancy and employer attraction on employer brand loyalty - Mohamad, Siti Fatimah; Md Sidin, Samsinar; Zawawi, Dahlia; Boo, Huey Chern; Ho, Jo Ann; Abdul Salam, Siti Soleha (Panoply Consultancy, 2017)
Employer brand is a package of functional, economic and psychological benefits provided by employer that makes an organization a desirable place to work. If employers are not fulfilling the employer brand promised to employees, it influences the employees' intent to leave, disloyalty, and job search behavior. Several studies have investigated the existence of employer brand in organizations. However, these studies did not measure the discrepancy between what is offered and what is delivered to employees. On the other hand, employer attraction had never been empirically investigated from the perspective of current employees. Thus, the aim of this study is to determine the direct relationship between employer brand discrepancy and employer attraction towards employer brand loyalty. The sample for this study was full-time employees who worked in four- and five-star hotels in Kuala Lumpur and Putrajaya, Selangor, and Pahang. The instrument measured employer brand offering, employer brand delivery, employer attraction and employer brand loyalty. A total of 436 forms were analyzed for this study. The results revealed that employer brand discrepancy had a very small predictive power towards employer brand loyalty, with Beta = 0.155. On the other hand, employer attraction had a big influence towards employer brand loyalty, with Beta = 0.811. It can be concluded that the organizations in this study did not have appealing psychological contracts, but they had a significant attraction to its employees. It is anticipated that this study will shed some light on the issue of the employer brand, particularly within the hospitality industry context.